Evaluation of machinability and surface quality enhancement of material extrusion fabricated polylactic acid cylinders through lathe machining parameters - Bañón-García, Fermín; Martín-Béjar, Sergio; Bermudo-Gamboa, Carolina; Trujillo-Vilches, Francisco Javier; Sevilla-Hurtado, Lorenzo (Springer, 2026)
This study examines the effect of lathe machining parameters on the machinability and surface quality of polylactic acid (PLA) cylinders produced using material extrusion technology. The research focuses on the correlation between cutting parameters, machining temperature, and factors such as required machining force and associated power consumption. The aim is to improve the final product quality while reducing production times. The comparison between high-quality, time-intensive printed pieces and normally printed pieces complemented by a post-machining operation shows that incorporating a machining step significantly improves surface quality and operational efficiency. The critical examination of the machining temperature, which is essential due to the thermoplastic nature of PLA and its low glass transition temperature, highlighted the influence of cutting speed and feed rate. Overall, feed rate was identified as the dominant parameter controlling mechanical loading and surface roughness, whereas cutting speed primarily governed thermal response and instantaneous power demand. The integrated analysis supports a process window in which compressed air assistance mitigates heat accumulation and promotes stable chip evacuation. From a manufacturing perspective, printing at a productive layer height followed by a short turning operation provides a competitive route to achieve high quality rotational surfaces compared with fine layer FFF printing, particularly for batch production.
Keywords: Extrusión (Mecánica); Material extrusion technology; Turning; Machinability; Machining; PLA